Further differentiating item and order information in semantic memory: students' recall of words from the "CU Fight Song", Harry Potter book titles, and Scooby Doo theme song. Issue 1 (2nd January 2017) - Overstreet, Michael F.; Healy, Alice F.; Neath, Ian
ABSTRACT: University of Colorado (CU) students were tested for both order and item information in their semantic memory for the "CU Fight Song". Following an earlier study by Overstreet and Healy [(2011). Item and order information in semantic memory: Students' retention of the "CU fight song" lyrics. Memory & Cognition, 39, 251–259. doi:10.3758/s13421-010-0018-3 ], a symmetrical bow-shaped serial position function (with both primacy and recency advantages) was found for reconstructing the order of the nine lines in the song, whereas a function with no primacy advantage was found for recalling a missing word from each line. This difference between order and item information was found even though students filled in missing words without any alternatives provided and missing words came from the beginning, middle, or end of each line. Similar results were found for CU students' recall of the sequence of Harry Potter book titles and the lyrics of the Scooby Doo theme song. These findings strengthen the claim that the pronounced serial position function in semantic memory occurs largely because of the retention of order, rather than item, information.